Dragon Pearl - Lee, Yoon Ha (Disney-Hyperion, 2019)
"Min, a thirteen-year-old girl with fox-magic, stows away on a battle cruiser and impersonates a cadet in order to solve the mystery of what happened to her older brother in the Thousand World Space Forces." --